2018
DOI: 10.3390/polym10030303
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing the Strong Screening Effect of Polyhedral Oligomeric Silsesquioxane Nanoparticles in Hydrogen-Bonded Random Copolymers

Abstract: A series of poly(vinylphenol-co-methacryisobutyl polyhedral oligomeric silsesquioxane) (PVPh-co-PMAPOSS) random copolymers have been synthesized through free radical copolymerizations of acetoxystyrene with methacryisobutyl POSS monomer and subsequent hydrazine monohydratemediated hydrolysis of the acetoxyl units. These random copolymers were characterized using nuclear magnetic resonance spectroscopy (NMR), Fourier transform infrared spectroscopy (FTIR), gel permeation chromatography (GPC), and differential s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…There are two main approaches to incorporate POSS components in to the PI: physical blending and covalent grafting by surface modification. , The most common mode to introduce POSS into PI is covalent bonding. Huang et al reported a novel aminopropyl isobutyl POSS (Am-POSS) with single vertex activity and the POSS–PI composites with permittivity below 2.6 (Figure a).…”
Section: Construction Of Porous Structuresmentioning
confidence: 99%
“…There are two main approaches to incorporate POSS components in to the PI: physical blending and covalent grafting by surface modification. , The most common mode to introduce POSS into PI is covalent bonding. Huang et al reported a novel aminopropyl isobutyl POSS (Am-POSS) with single vertex activity and the POSS–PI composites with permittivity below 2.6 (Figure a).…”
Section: Construction Of Porous Structuresmentioning
confidence: 99%
“…Compared with inorganic materials, organic polymers usually possess lower moduli and poorer thermal stabilities and mechanical properties. The incorporation of inorganic nanoparticles (NPs) nanotubes, or nanosheets (e.g., clay [ 1 , 2 ]), graphene [ 3 , 4 , 5 ], carbon nanotubes [ 6 , 7 , 8 ], or polyhedral oligomeric silsesquioxanes (POSS) [ 9 , 10 , 11 , 12 , 13 ] into a polymer matrix is, however, a relatively simple approach toward improving its mechanical and thermal properties.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of inorganic nanoparticles into self-assembled BCPs in the form of block copolymer/nanoparticle (BCP/NP) composites, with the blends stabilized through specific interactions, has potential applications in nanodevices, photonics, and sensors [19][20][21][22][23]. Polyhedral oligomeric silsesquioxanes (POSSs) are particularly useful nanoparticles for the preparation of hybrid materials, because they typically have cage-like structures with dimensions of 1-3 nm [24][25][26][27][28][29]. In general, functionalized POSS NPs have been prepared with one, two, or eight functionalized units; we have discussed their effects on the self-assembled structures of BCP hybrid complexes in several previous reports [30][31][32].…”
Section: Introductionmentioning
confidence: 99%